Discovery of BMS-961955, an allosteric inhibitor of the hepatitis C virus NS5B polymerase. Issue 15 (1st August 2017) - Zheng, Barbara Zhizhen; D'Andrea, Stanley V.; Hanumegowda, Umesh; Knipe, Jay O.; Mosure, Kathy; Zhuo, Xiaoliang; Lemm, Julie A.; Liu, Mengping; Rigat, Karen L.; Wang, Ying-Kai; Fang, Hua; Poronsky, Chris; et al.
Graphical abstract: Abstract: The synthesis, structure-activity relationship (SAR) data, and further optimization of the metabolic stability and pharmacokinetic (PK) properties for a previously disclosed class of cyclopropyl-fused indolobenzazepine HCV NS5B polymerase inhibitors are described. These efforts led to the discovery of BMS-961955 as a viable contingency backup to beclabuvir which was recently approved in Japan for the treatment of HCV as part of a three drug, single pill combination marketed as Ximency TM .